A modeling‐based proposal for safe and efficacious reintroduction of bedaquiline after dose interruption: A population pharmacokinetics study - Keutzer, Lina; Akhondipour Salehabad, Yasamin; Davies Forsman, Lina; Simonsson, Ulrika S. H. (CPT: pharmacometrics and systems pharmacology, 2022)
Bedaquiline (BDQ) is recommended for treatment of multidrug‐resistant tuberculosis (MDR‐TB) for the majority of patients. Given its long terminal half‐life and safety concerns, such as QTc‐prolongation, re‐introducing BDQ after multiple dose interruption is not intuitive and there are currently no existing guidelines. In this simulation‐based study, we investigated different loading dose strategies for BDQ re‐introduction, taking safety and efficacy into account. Multiple scenarios of time and length of interruption as well as BDQ re‐introduction, including no loading dose, 1‐ and 2‐week loading doses (200 mg and 400 mg once daily), were simulated from a previously published population pharmacokinetic (PK) model describing BDQ and its main metabolite M2 PK in patients with MDR‐TB. The efficacy target was defined as 95.0% of the average BDQ concentration without dose interruption during standard treatment. Because M2 is the main driver for QTc‐prolongation, the safety limit was set to be below the maximal average M2 metabolite concentration in a standard treatment. Simulations suggest that dose interruptions between treatment weeks 3 and 72 (interruption length: 1 to 6 weeks) require a 2‐week loading dose of 200 mg once daily in the typical patient. If treatment was interrupted for longer than 8 weeks, a 2‐week loading dose (400 mg once daily) was needed to reach the proposed efficacy target, slightly exceeding the safety limit. In conclusion, we here propose a strategy for BDQ re‐introduction providing guidance to clinicians for safe and efficacious BDQ dosing.